2022
DOI: 10.3390/s22030731
|View full text |Cite
|
Sign up to set email alerts
|

Measurement System for Unsupervised Standardized Assessments of Timed Up and Go Test and 5 Times Chair Rise Test in Community Settings—A Usability Study

Abstract: Comprehensive measurements are needed in older populations to detect physical changes, initiate prompt interventions, and prevent functional decline. While established instruments such as the Timed Up and Go (TUG) and 5 Times Chair Rise Test (5CRT) require trained clinicians to assess corresponding functional parameters, the unsupervised screening system (USS), developed in a two-stage participatory design process, has since been introduced to community-dwelling older adults. In a previous article, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
(74 reference statements)
0
4
0
3
Order By: Relevance
“…An evaluation prototype was then developed based on these findings. In a final evaluation study, relevant experiences and suggestions for further improvements were derived from interim discussions based on guideline-based telephone interviews and focus groups with 37 participants ( 25 ).…”
Section: Theme 1: Design Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…An evaluation prototype was then developed based on these findings. In a final evaluation study, relevant experiences and suggestions for further improvements were derived from interim discussions based on guideline-based telephone interviews and focus groups with 37 participants ( 25 ).…”
Section: Theme 1: Design Processesmentioning
confidence: 99%
“…Therefore, we considered the cognitive and sensorimotor impairments in the development of the technology in the VERSA assessment by adapting the screen display (easily readable and large font, high contrast, simple presentation) and the instructions (simple, short, and precise information) ( 25 ). The PROMOTE app was designed to be straightforward to use, having only the minimum required functionalities, including large user interface elements and a simple screen design ( 43 ).…”
Section: Theme 3: Implications For Technology-based Interventions In ...mentioning
confidence: 99%
“…Nowadays, new technologies, such as wearable sensors or smartphone-embedded inertial sensors, have been created to evaluate the TUG performance of older persons ( 24 ). The validity of the unsupervised screening system using sensors (aTUG chair, hip-worn inertial sensor, light barriers, and the Intel ® RealSense™ D435 depth image cameras) was examined in a study by Fudickar et al ( 25 ). Their results showed that this system was a valid tool for evaluating TUG, with both light barriers and inertial measurement units demonstrating high correlations with conventional stopwatch measurement ( r = 0.73 and 0.78, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…B. partizipative Studie). Für die Beteiligung in der Technikentwicklung stehen unterschiedliche Modelle zur Verfügung, von denen am häufigsten das Human-centred design [19] genutzt wird. Der Entwicklungsprozess ist iterativ angelegt und besteht aus vier Phasen: die Analyse des Nutzungskontextes, Festlegung der Nutzungsanforderungen, der Entwurf von und die Evaluation der Gestaltungslösungen.…”
Section: Introductionunclassified
“…Ausgewertete Angaben aus den Transkripten der Fokusgruppen (FG) und Telefoninterviews (TI). ; 2 Entwicklungsprozess und Phasen anhand des Human-centred design[19].Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen. Vervielfältigung nur mit Zustimmung des Verlages.…”
unclassified